Tinjauan Yuridis Putusan Perkara Perdata Tentang Dugaan Penyelundupan Perjanjian Yang Menyebabkan Pemalsuan Jual-Beli - Robianti, Masayu; Firdaus, Elsa Illaila (Universitas Sang Bumi Ruwa Jurai, 2025)
This research employs normative and empirical juridical methods to examine a civil court decision between PT Cahaya Batu Limau and Vital Element Investment, concerning alleged contract smuggling and document forgery in a sale and purchase transaction. The case arose from an investment cooperation agreement that was unilaterally converted into a sale and purchase deed without one party’s consent, leading to a dispute over the validity of asset transfer. Findings indicate that altering a legal relationship without mutual consent violates Article 1320 of the Indonesian Civil Code, while the use of forged documents breaches Article 263 of the Criminal Code, creating both civil and criminal implications. The court's decision is significant for understanding the boundary between civil and criminal law and how the court evaluates bad faith and evidence. This study recommends strengthening legal protection in investment agreements and enforcing due diligence in drafting authentic deeds to prevent misuse that harms one of the parties